A national study of the prevalence and risk factors associated with peripheral arterial disease from China: The China Hypertension Survey, 2012–2015. (15th January 2019) - Wang, Zengwu; Wang, Xin; Hao, Guang; Chen, Zuo; Zhang, Linfeng; Shao, Lan; Tian, Ye; Dong, Ying; Zheng, Congyi; Kang, Yuting; Gao, Runlin; ,
Abstract: Background: Peripheral arterial disease (PAD) is the third leading cause of atherosclerotic vascular morbidity after coronary heart disease and stroke. Epidemiology data of PAD is very limited in low-income and middle-income countries. A national wide survey was conducted from October 2012 to December 2015 to assess the prevalence of PAD in China. Methods: Data from the China Hypertension Survey (CHS). In total, 56, 000 people aged 35 years or older were enrolled in this sub-survey for PAD, and 30, 025 participants were eligible for analysis. Ankle-brachial index was measured using an automated ABI device (WatchBP Office device Microlife, China). PAD was defined by ABI and Edinburgh Claudication Questionnaire. Results and conclusions: Overall, 6.6% (estimated 45.3 million) of the Chinese adult population age 35 years or older had PAD. The weighted prevalence of PAD increased significantly after aged ≥75 years. There were no significant differences in PAD prevalence between urban and rural residents, as well as between males and females. Among individuals with PAD, only 4.9% (95% CI: 0%–10.1%) were aware of their condition, 1.9% (95% CI: 0%–4.0%) received revascularization, and 0.2% (95% CI: 0%–0.4%) achieved ABI >0.9. Older age, Han population, current smokers, education level, hypertension, CAD, diabetes, dyslipidemia, and rural residences all were significantly associated with an increased risk of PAD. In China, there is an increasing prevalence of PAD, but the awareness, treatment, and control were very low. Special attention should be paid to prevent and control PAD in China. Clinical trial registration number: ChiCTR-ECS-14004641. Highlights: Overall, 6.6% (estimated 45.3 million) of the Chinese adult population age 35 years or older had PAD. The weighted prevalence of PAD increased significantly after aged ≥75 years. Among individuals with PAD, 4.9% were aware of their condition, 1.9% received revascularization, and 0.2% achieved ABI >0.9. Older age, Han population, current smokers, education level, and rural residences can increase the risk of PAD.